Islam and Ecology: Gender Dynamics in Employee Green Behavior (EGB) among Muslim Employees - Kurnia Sari Kasmiarno; Dony Darma Sagita; Muhammad Fakhri Al-Kahfi; Hasta Dwi Pradana; Dio Bimo Saputro; Sari Wardani Simarmata (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze gender-based differences in Employee Green Behavior (EGB) among Muslim employees. EGB refers to pro-environmental actions voluntarily undertaken by employees in support of environmental sustainability in the workplace. This study used a quantitative approach with a cross-sectional survey design and involved 226 Muslim respondents (111 men and 115 women) from various industrial sectors in Indonesia. The instrument used was a five-item EGB scale adapted from Norton et al. (2015), with a reliability of α = 0.83. Data analysis was conducted using an independent t-test to test differences in EGB scores based on gender. The results showed that there were significant differences in most dimensions of EGB, with female employees consistently showing higher scores than male employees. The largest difference was in the habit of bringing reusable cutlery/drinking utensils. This finding reflects the influence of gender identity and religiosity in shaping environmentally friendly behavior. The Islamic perspective that places humans as caliphs on earth is an important ethical foundation for Muslim employees in internalizing ecological responsibility. This study suggests the importance of developing sustainability programs that are sensitive to gender differences and religiosity, as well as the need for specific strategies to increase male employees' engagement in environmentally friendly behaviors in order to achieve organizational sustainability goals more inclusively and effectively.